Spatial Distribution of Rn, CO2, Hg, and H2 Concentrations in Soil Gas Across a Thrust Fault in Xinjiang, China - Xiang, Yang; Sun, Xiaolong; Liu, Dongying; Yan, Long; Wang, Bo; Gao, Xiaoqi (Frontiers in Earth Science, 2020)
Spatial distribution characteristics and origin of soil gasses were discussed in this study. We also examine the correlation between the spatial variation of soil gasses and fault activity, based on the measurements of Rn, Hg, H2, and CO2 concentrations in the eastern segment of the BLT fault zone in the southern Tianshan Mountains, Xinjiang, China. The results show that the Rn and CO2 concentrations on the hanging wall were higher than those near the fault zone and on the footwall of the fault. Moreover, the Hg and H2 concentrations on the footwall were also higher than those near the fault and on the hanging wall of the fault. The main factors affecting the variations in soil gas spatial distribution were gaseous origin structure of the crust, fault activity, fault fracture degree, stratigraphic lithology, and the cover layer. The results of active structural fault mapping show that the BLT fault has been active since the Late Quaternary and the thrust has broken the fault surface. Under the influence of tectonic compressive stress, the tension zone was formed on the hanging wall of the fault and fractures were developed. This result is consistent with the characteristics of soil gas concentrations measured in this study, indicating that the concentrations of Rn, Hg, H2, and CO2 are closely related to the fault activity. These findings can be applied to identify seismic precursors from gas monitoring data of the studied area.